Thinking Place: Animating the Indigenous Humanities in Education - Battiste, Marie; Bell, Lynne; Findlay, Isobel M.; Findlay, Len; Henderson, James (Sákéj) Youngblood (The Australian Journal of Indigenous Education, 2005)
Abstract Illustrating contexts for and voices of the Indigenous humanities, this essay aims to clarify what the Indigenous humanities can mean for reclaiming education as Indigenous knowledges and pedagogies. After interrogating the visual representation of education and place in Saskatoon, Saskatchewan, Canada, the essay turns to media constructions of that same place as an exemplary site for understanding Aboriginal relations to the Canadian justice system, before sharing more general reflections on thinking place. The task of animating education is then resituated in the Indigenous humanities developed at the University of Saskatchewan, Canada, as a set of intercultural and interdisciplinary theoretical and practical interventions designed to counter prevailing notions of colonial place. The essay concludes by placing education as promise and practice within the non-coercive normative orders offered by the United Nations. In multiple framings and locations of the Indigenous humanities, the essay aims to help readers to meet the challenges they themselves face as educators, learners, scholars, activists.